Pengaruh Video Animasi Terhadap Hasil Belajar Kognitif Siswa Kelas IV SDN Kepuh Kiriman I Waru Sidoarjo - Amania Nazilah; Ida Sulistyawati; Pana Pramulia (UNIVERSITAS PGRI YOGYAKARTA, 2025)
AbstractThis research was carried out because in one lesson the teacher still separated the subject matter that should be contained thematically. In addition, the learning process is not optimal because students experience adjustments due to the implementation of online learning. So, the provision of learning media is very important in the learning process, one of which is using animated videos. The purpose of this study was to describe the effect of animated video on cognitive learning outcomes of fourth grade students at SDN Kepuh Kiriman I Waru Sidoarjo. This research is included in the type of true experimental, with a posttest-only control design. The research subjects were 51 students. The results obtained from the experimental class amounted to 2,292 with an average of 91.68 and the highest score was 100 as many as 6 students. While the score in the control class was 2,096, with an average of 80.62 and the highest score was 100, with 3 students. The results of the calculation of hypothesis testing using SPSS version 26 software are proven by a significant value of 0.000 which means a value less than 0.05 indicates Ho is rejected and Ha is accepted. So, it can be concluded that animated videos have a very good effect on cognitive learning outcomes for fourth grade students at SDN Kepuh Kiriman I Waru Sidoarjo.Keywords: animated video, learning outcomes.